Peroxynitrite induces F-actin depolymerization and blockade of myosin ATPase stimulation - Tiago, Teresa (2012)
Treatment of F-actin with the peroxynitrite-releasing agent 3-morpholinosydnonimine (SIN-1) produced a dose-dependent F-actin depolymerization. This is due to released peroxynitrite because it is not produced by ‘decomposed SIN-1’, and it is prevented by superoxide dismutase concentrations efficiently preventing peroxynitrite formation. F-actin depolymerization has been found to be very sensitive to peroxynitrite, as exposure to fluxes as low as 50–100 nM peroxynitrite leads to nearly 50% depolymerization in about 1 h. G-actin polymerization is also impaired by peroxynitrite although with nearly 2-fold lower sensitivity. Exposure of F-actin to submicromolar fluxes of peroxynitrite produced cysteine oxidation and also a blockade of the ability of actin to stimulate myosin ATPase activity. Our results suggest that an imbalance of the F-actin/G-actin equilibrium can account for the observed structural and functional impairment of myofibrils under the peroxynitrite-mediated oxidative stress reported for some pathophysiological conditions.